Dualistically burned out? : The development of school and sport burnout symptoms and its relation to self-esteem among dual-career students in Finnish sport high schools - Hallama, Saara (My University, 2021)
Being involved in high-level sports alongside an intensive educational program is a challenging combination, yet a challenge that dual-career high school student-athletes are expected to face. As performing well in both domains requires a lot of physical and mental stamina, it is not unlikely that students might exhibit an increased amount of burnout symptoms. Burnout is widely studied in both the academic and athletic domain, but to investigate them together and assess how they are related has been left unstudied until recently. The main aim of the current study was to find out whether there is a difference between burnout symptom rates in the academic and athletic domain among Finnish dual-career students. We further investigated the development of this relation, as we assessed how similar or different burnout symptom rates were in the beginning and end of high school. In addition, we investigated how self-esteem is related to burnout symptoms in both domains. The current study is part of a longitudinal project called “Winning in the long run”, which started in Finland in 2015. The aim of the project was to follow and get insight into the psychosocial development and academic orientation of dual-career students in high school. Extensive questionnaires were administered 5 times throughout the high school period assessing among other things motivation, identity, burnout and self-esteem. In total 228 dual-career students answered the questionnaires of our interest at the beginning (T1) and end of high school (T5). School and sport burnout symptoms were measured with an adapted version of SBI-9, while self-esteem was measured with an abridged RSES. The results indicated that initially youngsters had stronger school burnout symptoms than sport burnout symptom, but the gap between these diminished towards the end of high school. Negative correlations were found at both time points between burnout symptoms and self-esteem across domains. Severe burnout symptoms on a group level are nevertheless not found. Our results thus indicate that burnout symptoms for dual career youngsters slightly increase during high school years, may transfer from one domain to another and are associated with low self-esteem. These findings should be considered when planning the challenging route of a dual career. Most importantly, youngsters should be provided with enough information and guidance to balance between being a promising athlete as well as a successful student.
Keywords: burnout, self-esteem, domain-specificity, dual-career, high school, youngster